2013
DOI: 10.1093/hmg/ddt484
|View full text |Cite
|
Sign up to set email alerts
|

WNT/β-catenin signalling is activated in aldosterone-producing adenomas and controls aldosterone production

Abstract: Primary aldosteronism (PA) is the main cause of secondary hypertension, resulting from adrenal aldosterone-producing adenomas (APA) or bilateral hyperplasia. Here, we show that constitutive activation of WNT/β-catenin signalling is the most frequent molecular alteration found in 70% of APA. We provide evidence that decreased expression of the WNT inhibitor SFRP2 may be contributing to deregulated WNT signalling and APA development in patients. This is supported by the demonstration that mice with genetic ablat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
151
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 168 publications
(166 citation statements)
references
References 65 publications
9
151
0
5
Order By: Relevance
“…Familial adenomatous polyposis coli and mutations of APC " Activation of the Wnt/b-catenin signaling pathway is involved in adrenal tumors, especially non-cortisolproducing adenomas and adrenocortical carcinomas (31). Patients with familial adenomatous polyposis (FAP) (OMIM #175100) present multiple colonic polyps and an increased risk of early colon carcinomas and various adrenocortical tumors, including non-functional cortisol producing adenoma, adrenocortical cancer (31) and bilateral macronodular adrenal hyperplasia (10,32).…”
Section: Multiple Tumors Syndromes Associated With Pbmahmentioning
confidence: 99%
“…Familial adenomatous polyposis coli and mutations of APC " Activation of the Wnt/b-catenin signaling pathway is involved in adrenal tumors, especially non-cortisolproducing adenomas and adrenocortical carcinomas (31). Patients with familial adenomatous polyposis (FAP) (OMIM #175100) present multiple colonic polyps and an increased risk of early colon carcinomas and various adrenocortical tumors, including non-functional cortisol producing adenoma, adrenocortical cancer (31) and bilateral macronodular adrenal hyperplasia (10,32).…”
Section: Multiple Tumors Syndromes Associated With Pbmahmentioning
confidence: 99%
“…One potential mechanism could be the activation of the WNT/b-catenin pathway. Indeed, it has been shown that this pathway is activated in w70% of APA (Boulkroun et al 2011, Berthon et al 2014), that in rare cases somatic activating mutations of CTNN1B, coding for b-catenin, have been described in APA (Azizan et al 2013, Scholl et al 2013 and that constitutive b-catenin activation in the adrenal cortex induces ectopic ZG differentiation and dedifferentiation of the orthotopic ZF, resulting in hyperaldosteronism in 10-month-old mice (Berthon et al 2010). However some of these mice develop malignant characteristics, such as uncontrolled neovascularization and local invasion, a phenotype rarely observed in patients with PA (Berthon et al 2010); it is possible that the levels of b-catenin dosage play a role in the development of specific types of tumors within the adrenal cortex (Berthon et al 2014).…”
Section: Familial Hyperaldosteronism Type IImentioning
confidence: 99%
“…Activation of the β-catenin pathway is restricted to the ZG (Kim et al 2008;Walczak et al 2014), and ectopic expression leads to the activation of ZG markers in ZF cells (Berthon et al 2010). Moreover, β-catenin seems to bind to and control the expression of At1r, a gene specifically expressed within the ZG (Berthon et al 2014). Finally, stochastic deletion of β-catenin using a low-level expressing Sf1-Cre line leads to progressive loss of the adrenal cortex in adult life (Kim et al 2008).…”
mentioning
confidence: 99%